Conceptual design of elliptical cavities for intensity and position sensitive beam measurements in storage rings - Sanjari, Mohammad Shahab; Chen, Xin; Hülsmann, Peter; Litvinov, Yuri A.; Nolden, Fritz; Piotrowski, Jeremi; Steck, M.; Stöhlker, Thomas (Physica scripta, 2015)
Position sensitive beam monitors are indispensable for the beam diagnostics in storage rings. Apart from their applications in the measurements of beam parameters, they can be used in non-destructive in-ring decay studies of radioactive ion beams as well as enhancing precision in the isochronous mass measurement technique. In this work, we introduce a novel approach based on cavities with elliptical cross-section, in order to compensate the limitations of known designs for the application in ion storage rings. The design is aimed primarily for future heavy ion storage rings of the FAIR project. The conceptual design is discussed together with simulation results.
Gesehen am 16.06.2020